2012
DOI: 10.1183/09031936.00187811
|View full text |Cite
|
Sign up to set email alerts
|

Severity assessment of healthcare-associated pneumonia and pneumonia in immunosuppression

Abstract: The study compares the ability of the PSI (pneumonia severity index), CURB-65 (confusion, urea >7 mol·L(-1), respiratory rate ≥ 30 breaths·min(-1), blood pressure <90 mmHg systolic or ≤ 60 mmHg diastolic, and age ≥ 65 yrs), CURB and CRB-65 scales and the Severe Community-Acquired Pneumonia (SCAP) score to predict 30-day mortality in healthcare-associated pneumonia (HCAP) patients, and analyses differences in the demographics, aetiology and outcomes of community-acquired pneumonia (CAP), HCAP and pneumonia in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 36 publications
6
38
1
1
Order By: Relevance
“…(16) The findings of these studies suggest that the conventional prognostic guidelines used for CAP are not appropriate for the evaluation of HCAP severity. (15,16) In the present study, we found that I-ROAD correctly reflected the severity of CAP and HCAP, whereas A-DROP and CURB-65 underestimated the severity of both. PSI was useful in evaluating the severity of CAP and HCAP, but there was no statistically significant difference between the two groups.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…(16) The findings of these studies suggest that the conventional prognostic guidelines used for CAP are not appropriate for the evaluation of HCAP severity. (15,16) In the present study, we found that I-ROAD correctly reflected the severity of CAP and HCAP, whereas A-DROP and CURB-65 underestimated the severity of both. PSI was useful in evaluating the severity of CAP and HCAP, but there was no statistically significant difference between the two groups.…”
Section: Discussionsupporting
confidence: 54%
“…Carrabba et al found that PSI and SCAP (severe community-acquired pneumonia) (14) are useful prognostic tools for immunocompetent patients, with the former noted to be highly sensitive but poorly specific for the evaluation of HCAP severity in immunocompromised patients with HCAP. (15) In a different study, Jeong et al demonstrated that the prognostic powers of PSI and CURB-65 for 30-day mortality were significantly lower for patients with HCAP than for patients with CAP. (16) The findings of these studies suggest that the conventional prognostic guidelines used for CAP are not appropriate for the evaluation of HCAP severity.…”
Section: Discussionmentioning
confidence: 98%
“…A previous report 26 showed prognostic scoring, including PSI, was good for predicting mortality in nonimmunocompromised patients with HCAP. Another study 27 also suggested that PSI could be applied to assess the severity of illness in the management of patients with HCAP, although the discriminatory powers of PSI for 30-day mortality were significantly lower in patients with HCAP compared with community-acquired pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that 17.3-38.0% of outpatients with pneumonia suffer from HCAP [2][3][4][5][6] , and its mortality is about 20%, which is approximately twice that of communityacquired pneumonia (CAP) [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%